The Relationship Between Health Belief and Self Acceptance and Self Management Behavior in Pulmonary Tuberculosis Clients in The Work Area of The Japan Kudus Health Center - Aulia Chusna, Arda; Hartinah, Dewi; Jauhar, Muhamad (CV. Inara, 2026)
The study discusses pulmonary tuberculosis as a chronic infectious disease that is still a global health problem, with Indonesia ranking third in the world. The increase in tuberculosis cases is influenced by drug resistance, limited access to health services, and poor environmental hygiene conditions. Kudus Regency, especially the work area of the Japanese Health Center, is an area with a relatively high number of tuberculosis cases. This disease not only has an impact on the physical condition, but also affects the mental and social aspects of the patient, so that self-management skills are an important factor in the success of treatment. The Health Belief Model explains that an individual's perception of susceptibility, disease severity, benefits, and barriers to health measures plays a role in shaping health behavior. In addition, good self-acceptance can improve treatment adherence and coping ability of patients. Self-management includes medication adherence, symptom management, and lifestyle changes influenced by social support, education level, and understanding of disease. This study used a correlational design with a cross sectional approach and involved 53 respondents who were selected through purposive sampling techniques. The research instruments include the Health Belief Model questionnaire, self acceptance, and self-management. Data analysis was carried out univariate and bivariate using the chi square test. The results showed that most of the respondents had a high health belief of 79.2 percent and a high self-acceptance of 75.5 percent. The majority of respondents' self-management was in the good category, namely 94.3 percent. The bivariate test showed a significant relationship between health belief and self-management with a p value of 0.044 and an odds ratio of 9.111. In addition, there was a significant relationship between self acceptance and self-management with a p value of 0.02 and an odds ratio of 1.193. The conclusion of this study shows that health belief and self acceptance are meaningfully related to the self-management behavior of tuberculosis clients, so education and psychosocial support need to be improved on an ongoing basis.